Prinsip Dasar Pendidikan Islam dalam Memilih Pemimpin - Ali Nurdin (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Leadership is very important, and what is even more important is how we don't make mistakes in choosing leaders. Because mistakes in choosing a leader will lead to disaster in the management of a system, both an organization and a government institution. This research tries to examine the problems in determining leader criteria and principles for selecting leaders in the context of Islamic education. The method approach used in this research is a literature study where data processing tests the theoretical suitability of the principles of Islamic Education. The results of the literature study show that the principles of choosing leaders in Islam must of course be correlated with the principles of choosing leaders so that the same interests are found and there is trust between the leader and those being led.